Exploring the Influence of YouTube Videos on Purchase Intentions among Millennial Consumers in Tasikmalaya City - Nugraha, Ferryan (International Journal of Multidisciplinary Approach Research and Science, 2023)
The paradigm of consumer purchase decisions has been altered by the digital marketing landscape. Presently, consumers actively seek reliable and truthful information to assist them in their purchasing decisions. A noteworthy group in this regard is the Millennial generation, who dedicate a substantial amount of their time to online activities, with a particular focus on social media platforms. This generation, often referred to as "technology savvy," demonstrates their reliance on technology and employs it for various decisions that impact them, including their purchasing intentions. Prior to making a purchase, Millennial extensively research product information and align it with their individual needs and interests. The objective of this research was to examine the impact of user-generated content (UGC) on the purchasing intentions of Millennials in Tasikmalaya city. The investigation was conducted utilizing the prominent social media platform, YouTube. The primary aims of this research were to identify the factors that influence purchasing intentions and to comprehend the attitudes of Millennials towards purchasing after watching product-related videos on YouTube.To achieve these goals, the researcher administered an online questionnaire to individuals who had viewed smartphone product videos on YouTube. The questionnaire, comprising 350 valid responses, served as the means to test the hypotheses using the Structural Equation Modelling approach. The research yielded significant findings, that factors such as video quality, duration, and the adeptness and delivery of the presentation are crucial in influencing the purchase decisions of Millennial consumers. In summary, these findings imply that those aspects play a substantial and positive role in heightening the purchase intentions of Millennials in Tasikmalaya City.